Monetary policy in the context of the financial crisis new challenges and lessons - Barnett, William A.; Jawadi, Fredj (Bingley, U.K. : Emerald, 2015)
ISETE 24 analyses monetary policies and central bank actions in the context of the recent global financial crisis. Part 1 discusses standard monetary policies and inflation targeting rules. Those approaches were appropriate to reaching two main objectives during the great moderation: controlling inflation and accommodating economic growth. But the end of the great moderation revealed the inadequacy of such monetary policies during the rapid development of financial and credit markets. Speculative bubbles, revealing financial instabilities, resulted in a credit crunch, a global financial crisis, and economic depression for major economies. Part II focuses on the non-conventional monetary policies introduced recently by several central banks. New monetary rules and variations in these rules are documented. Besides the well-known targets of monetary policy (inflation, unemployment, and economic growth), these new rules often target asset prices to moderate the development of financial markets and the volatility of financial cycles. ISETE 24 also investigates the effects of non-conventional monetary policies on developing and emerging economies and issues of alternative finance.
Adoption of inflation targeting and economic policies performance in emerging countries : a dynamic treatment effect evaluation / Mohamed Kadria, Mohamed Safouane Ben Aissa -- Careful price level targeting / George A. Waters -- Are price dynamics homogenous across emerging Europe? Empirical evidence from panel data / Iuliana Matei -- The global component of local inflation : revisiting the empirical content of the global slack hypothesis with Bayesian methods / Enrique Marti<U+0301>nez-Garci<U+0301>a -- Pass-through of exchange rate shock to prices in the Euro area : evidence from pricing chain model / Nidhaleddine Ben Cheikh, Wae<U+0308>l Louhichi -- Escape routes from sovereign default risk in the Euro area / Willi Semmler, Christian R. Proan<U+0303>o -- Actual versus perceived Taylor rules : how predictable is the European Central Bank? / Nikolay Markov -- A regime switching model for the European Central Bank / Nikolay Markov -- International trade imbalance : the amplification of monetary policy effects through financial markets / Qiheng Han, Junqing Li, Jianbo Zhang -- Modern monetary rules : any role for financial targeting? / Marcin Wolski -- The Taylor rule, the zero lower bound and the term structure of interest rates / J. Huston McCulloch -- A comparison of the Feds and ECBs strategies during the subprime crisis / Marcel Aloy, Gilles Dufre<U+0301>not -- Was Bernanke right? Targeting asset prices may not be a good idea after all / Tiziana Assenza, Michele Berardi, Domenico Delli Gatti -- Shareholding relationships and financial crisis : a network analysis / Nicolo<U+0300> Pecora, Alessandro Spelta -- Finance otherwise : the end of banks? / Michel Roux.
Print version record
Keywords: Business & Economics -- Econometrics; Econometrics; Monetary policy; Monetary policy -- Econometric models; Global Financial Crisis, 2008-2009.